KAJIAN ASPEK LINGKUNGAN DALAM PENGEMBANGAN AGROEKOWISATA PADA SISTEM SUBAK - Sumiyati, Sumiyati; Sutiarso, Lilik; Windia, Wayan; Sudira, Putu (Bumi Lestari; Vol 12 No 2 (2012), 2012)
Along with the development of the tourism in Bali, one of the phenomena occurs was that the land conversion to the non-agricultural land and pollution, and increased water demand not only for irrigation. These conditions affect the sustainability of the subak system. One strategy to support the sustainability of the subak system is the synergy between agriculture (Subak) to tourism, which developed agroecotourism on the subak system. It must consider the physical and social environment. The purpose of this study is to analyze the existing condition of Subak in Bali and if it made the development agroecotourism on the subak systems. This is about the quality of irrigation water, the physical condition of irrigation facilities, subak system facilities, and socio-cultural conditions of subak system. Water quality in Subak Anggabaya, Subak Lodtunduh, and Subak Padanggalak with the development of Kertalangu agrotourism, is in good condition. It could be argued that if made ??the development of agroecotourism on the subak systems, irrigation water quality can still be maintained in good condition are used for agriculture. The value of physical conditions on Subak Anggabaya was 2.00 (moderate) and at the Subak Lodtunduh are 2.00. With the development of agroecotourism on the subak systems be 2.21 on Subak Anggabaya and 2.23 on Subak Lodtunduh. A Socio cultural condition on subak system management to support the development of agroecotourism area, at Subak Anggabaya was 2.00 (moderate) and at the Subak Lodtunduh are 2.23 (between moderate and good). With expected agroecotourism visitors activities can provide positive influence (3.00) to the local community and the socio cultural conditions of subak system can increase or better.
Keywords: subak, agroecotourism, fuzzy logic, study of environment aspect